O estágio supervisionado em administração pública no Brasil : entre virtudes e vicissitudes, identificadas e avaliadas no curso da UNESP de Araraquara - Ramalheiro, Geralda Cristina de Freitas (2016)
Throughout history, the teaching of Public Administration has gone through several crises, experienced moments of glory , others of retraction others of expansion and legitimation and now experience the maturity in the search for own contours that were provided by own curriculum guidelines of the Public Courses. One of the pedagogical tools used in conciliation process of theory with practice is the internship. Public administration programs worldwide, include mandatory or optional internship in their curriculum grid. As a result, thousands of worldwide university students participate in Internship programs in public agencies. The objective of this dissertation will be to analyze the internship from the optics of the teaching complementation in public administration, checking the difficulties, the virtues and the benefits provided by the achievement of internship. Concurrently, will seek to analyze the relationship between the internship and the pedagogical projects of a sample of public administration courses. Another objective is to research the internship influence about student’s decision to remain or not in the public career. To materialize the objective of this dissertation, will be used a methodological strategy which is explained in the following expressions: exploratory research with purpose made possible by qualitative method, according to the inductive logic and outlined such as unique case study (internships in public administration courses of UNESP - Araraquara). Operationally, it is indicated that this search will be performed based on triangulation of three methods: documentary research, fulfillment of interview and application of survey questionnaires. What became clear is that the stage in the Public Course aims to complement the education and is an opportunity for professional experience in many education institutions, whose main focus is to deepen the knowledge and the fiscal year of training. In UNESP the experience lacks systematization, is a practice not gestated and undervalued.